Peran Status Sosial Ekonomi dan Dukungan Orang Tua terhadap Performa Akademik Peserta Didik di SMA Negeri 3 Tondano - Hasran; Lalogiroth, Benedikta Firginia; Pangalila, Theodorus (Tumoutou Social Science Journal, 2024)
This study aims to investigate the role of socioeconomic status and parental support on the academic performance of students at SMA Negeri 3 Tondano. In the context of education, both factors are considered crucial in determining student success. A favorable socioeconomic status often provides greater access to learning resources and educational facilities, while parental support plays an important role in building students' motivation and self-confidence. Through surveys and interviews, this research collected data from students, parents, and teachers. The results indicate that students with higher socioeconomic status tend to have better academic performance; however, emotional and academic support from parents also significantly influences learning outcomes. Therefore, this study recommends the need for policies that enhance parental support and efforts to reduce socioeconomic disparities in order to create a better learning environment for all students.